2021
DOI: 10.1186/s12884-021-03754-0
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth and infant death: mental health among low-income mothers in Mumbai

Abstract: Background India has the highest number of stillbirths and the highest neonatal death rate in the world. In the context of its pronatalist society, women who experience perinatal loss often encounter significant social repercussions on top of grief. Furthermore, even when pregnancy outcomes were favorable, adverse life circumstances put some women at risk for postnatal depression. Therefore, perinatal loss and postnatal depression take a heavy toll on women’s mental health. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The inconsistency in the prevalence of anxiety and depression may partly be explained by the inconsistency of measurement tools and time since stillbirth that data were collected. When using the same scale and diagnostic criteria, the results of previous studies and ours were similar [ 31 , 32 ]. Another explanation could be cultural differences, which may lead to differences in cognitive and psychological responses to TOPFA.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The inconsistency in the prevalence of anxiety and depression may partly be explained by the inconsistency of measurement tools and time since stillbirth that data were collected. When using the same scale and diagnostic criteria, the results of previous studies and ours were similar [ 31 , 32 ]. Another explanation could be cultural differences, which may lead to differences in cognitive and psychological responses to TOPFA.…”
Section: Discussionsupporting
confidence: 78%
“…One explanation for this finding is that fathers with high income levels have good material security to reduce worries about the cost of treatment and rehabilitation for their wives. Additionally, they may pay more attention to mental health and be more active in seeking support to meet their psychological needs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The women in this study live in established slums, which are close-knit communities that, for many, provide a sense of social support [ 65 ]. However, it should be noted that at baseline women in the current sample indicated that they had low social support, which was significantly associated with HSCL in our regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These subscales, Wishful Thinking and Practical Coping are each constructed of seven items measuring two distinct coping styles and has previously been used in India. 30 , 31 Each subscale is summed separately with higher scores (0–21) indicating greater use of either coping style. Cronbach’s α = 0.77.…”
Section: Methodsmentioning
confidence: 99%
“…A 7-item scale measuring positive and negative religious coping (three items each), as well as one item regarding overall intrinsic religiosity, has previously been used in similar populations. 31 , 32 Higher scores indicate more use of positive or negative religious coping (possible scores of 3–12 each) and greater identification with intrinsic religiosity (possible score of 1–4). 33 Positive religious coping subscale Cronbach’s alpha = 0.89.…”
Section: Methodsmentioning
confidence: 99%